First record of rare dobsonfly species Acanthacorydalis asiatica (Wood-Mason, 1884) (Megaloptera: Corydalidae: Corydalinae) in Myanmar - Bolotov, Ivan N.; Tumpeesuwan, Sakboworn (Zootaxa, 2014)
The species in the dobsonfly genus Acanthacorydalis van der Weele, 1907 (Megaloptera: Corydalidae: Corydalinae) are some of the largest freshwater insects in the World. It is a small genus occurring only in Asia and currently comprises eight species, seven of which are restricted to the Oriental Realm (Glorioso 1981; Liu et al. 2005; Yang & Liu 2010; Cao & Liu 2013). Six species are known from China (four considered endemic), two from India, and two species occur in Vietnam (Liu et al. 2005; Yang & Liu 2010; Letardi et al. 2012). Glorioso (1981) noted that the geographical range of the genus extended from northeastern India to Vietnam. No records of Acanthacorydalis are currently available from Myanmar.